Eksplorasi Dokumentasi Dan Representasi Artefak Budaya Dalam Realitas Virtual 3D Sebagai Bentuk Pengarsipan Digital - slamet riyadi; Arianti Ayu Puspita; Meirina Triharini; Prananda Luffiansyah Malasan; Raditya Ardianto Taepoer; Achmad Syarief (Jurnal Desain Indonesia., 2025)
Preserving cultural artifacts is essential for safeguarding heritage and advancing art and design research. Conventional documentation methods often fail to capture the intricate physical and material details of artifacts. This study explores the use of three-dimensional scanning technologies, such as Structured Light Scanning (SLS), Light Detection and Ranging (LiDAR), and photogrammetry, as an effort to digitally archive cultural artifacts. These techniques generate detailed digital models that accurately represent the artifacts’ shapes, dimensions, and material properties. The digital models undergo refinement in Blender, a 3D modeling software, to reduce polygon counts, repair deformations, and optimize textures. The refined models are then integrated into a virtual platform developed with Unreal Engine. This platform provides immersive experiences through virtual reality (VR), enabling audiences to explore and interact with the artifacts in realistic virtual environments. Additionally, the VR environment offers insights into spatial contexts, such as the placement of objects and their proportional relationships within traditional settings. By exploring various 3D scanning methods, the study offers recommendations for selecting appropriate techniques based on specific needs and field conditions. The findings emphasize the importance of accurate scanning and post-processing to ensure artifacts are usable in VR. This approach ensures optimal viewing performance and creates culturally immersive experiences that connect users to their historical origins.